What Do Indonesian and Dutch Teachers Find Challenging When Implementing Realistic Mathematics Education? - Puri Pramudiani; Tatang Herman; Turmudi Turmudi; Maarten Dolk; Belinda Terlouw (Jurnal Pendidikan Matematika, 2023)
At the end of the sixties of last century, the development of Realistic Mathematics Education (RME) started in the Netherlands. At the beginning of this century, the Indonesian adaptation of RME, Pendidikan Matematika Realistik Indonesia (PMRI), started. The implementation of RME / PMRI has proven to be challenging. In this research, a qualitative case study was used to investigate teachers’ perceptions and experiences in implementing RME/PMRI in their classes. Semi-structured interviews were conducted with several Dutch and Indonesian teachers who have joined the RME/PMRI training. We found similarities and differences between the two groups of teachers. Both groups of teachers understand the use of context as a starting point for students to construct mathematical understanding. The Dutch teachers considered the construction of interesting mathematical problems and the use of the guided-reinvention principle as the difficulties but motivated them to do more practice. Indonesian teachers mentioned that for them, the integration of mathematics with other subject areas for integrated thematic learning in the 2013 curriculum was their constraint but it was also a challenge for them to be more creative. These perspectives can become a reference for the development of a localized implementation of learning trajectory in classroom practices.